Implementation of Character Education in Social Sciences Learning aAt Vii Grade Students of Smpn 1 Sungai Geringging, Padang Pariaman Regency - Roza Linda; Buchari Nurdin (International Journal of Educational Dynamics, 2021)
This research was motivated by the many students who do character deviation during the school's learning process and the surrounding environment. Therefore, this study aims to analyze the character education program in social studies learning—implementation of character education in social studies learning. Character education constraints in social studies are learning. This type of research was qualitative. There were three primary data sources, consisting of one principal and two teachers in social studies subjects. The data used were primary data and secondary data, where the data analysis included four activity streams, namely the process of data collection, data reduction, data presentation, and conclusion/verification. The results showed that the character education program had been programmed, both in general and specifically in the social studies subject. Meanwhile, five character values are applied: the value of discipline, respect, and attention, perseverance, the value of responsibility, and accuracy. This program has been implemented through social studies subjects. Cultivating character values is adjusted to each meeting's learning material so that not all meetings can be applied—5 character values selected for social studies learning.